Sevoflurane induces inflammation in primary hippocampal neurons by regulating Hoxa5/Gm5106/miR-27b-3p positive feedback loop. Issue 2 (20th December 2021) - Zhu, Zifu; Ma, Li
ABSTRACT: Postoperative cognitive dysfunction (POCD) is a normal condition that develops after surgery with anesthesia, leading to deterioration of cognitive functions. However, the mechanism of POCD still remains unknown. To elucidate the POCD molecular mechanism, sevoflurane was employed in the present study to generate neuroinflammation mice model. Sevoflurane treatment caused inflammatory markers IL6, IL-10 and TNF-α high expression in primary hippocampal neurons and blood samples. Long non-coding RNA Gm5106 was found to be increased after being stimulated with sevoflurane. Silencing Gm5106 inhibited neuron inflammation. In the meanwhile, Gm5106 was identified as a direct target of miR-27b-3p that was inhibited by sevoflurane and related to inflammation suppression. In addition, transcription factor (TF) Hoxa5 was validated to activate Gm5106 through two binding motifs in the promoter region after sevoflurane exposure. Furthermore, miR-27b-3p also directly targeted Hoxa5 3ʹUTR, which affected nuclear Hoxa5 protein served as TF. Hoxa5 protein instead of 3ʹUTR reduced miR-27b-3p, in which Gm5106 knocking down abrogated this effect. In conclusion, sevoflurane induces neuroinflammation through increasing long non-coding RNA Gm5106, which is transcriptionally activated by Hoxa5 and directly targeted by miR-27-3p. Apart from that, Hoxa5, Gm5106, and miR-27b-3p form a positive feedback loop in sevoflurane stimulation.